Mechanical properties of cement composites reinforced with ceramic fiber - G. A. Zimakova; E. A. Kasper; O. S. Bochkareva (Архитектура, строительство, транспорт)
Reinforcing components and chemical additives are significant in modifying the structure of cement composites. Ceramic fibers, as a disperse-reinforcing component in cement systems, provide increased tensile strength in bending, crack resistance and durability of the material. The results of the research have revealed that such a concrete structure-forming component as ceramic mullite-silica fiber 0.02 to 0.06 mm across is rational to combine with a carboxylates-based chemical additive. Optimal dosages of mullite-silica fiber that influence the structure and physical-mechanical properties of the cement stone were determined. The method of scanning electron microscopy and spectral analysis was used to examine processes on the interface cement matrix – fiber. It has been underlined that fibers are covered by phase-forming hydrates due to structural and chemical correspondence. The use of ceramic fibers of high-temperature synthesis and water-reducing additive made it possible to increase the compressive strength of cement composites by 1.9 times compared to the control sample, as well as to improve the resistance of cement stone to destruction by increasing the bending tensile strength by 3.9 times and crack resistance by 2 times compared to the control composition.